THE EFFECT OF USING COLLABORATIVE STRATEGIC READING TECHNIQUE ON THE ABILITY OF STUDENTS IN COMPREHENDING NARRATIVE TEXTS - Oktapiani, Rama; Supriusman, Supriusman; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is aimed to find out if there is a significant effect of using Collaborative Strategic Reading technique on the ability of the first year students of Madrasah Aliyah Muhammadiyan Pekanbaru in comprehending narrative texts. The research design was a pre-experimental research with one group pre-test and post-test design. The population was the first year students in academic year 2019/2020. The sample was all the first year students (X IPA and X IPS) which consist of 35 students. The instrument used to collect the data was a reading test. The test consist of 40 items. The obtained data was analyzed by using SPSS version 23.0. The finding of the research showed that the mean score of post-test was higher than pre-test (76.00>70.03). The value of the t-test was higher than t-table (15.485>2.042) at 5% of significant level. Therefore, alternative hypothesis (Ha) was accepted. This means that Collaborative Strategic Reading technique was effective for teaching reading comprehension concerning narrative texts. It can be concluded that there is a significant effect of using Collaborative Strategic Reading technique on the ability of the first year students of Madrasah Aliyah Muhammadiyah Pekanbaru in comprehending narrative texts. In other words, teaching reading comprehension through Collaborative Strategic Reading technique is an effective way to solve the students’ problem on the reading comprehension.Key Words: Effect, Collaborative Strategic Reading technique, Reading Comprehension